2005
DOI: 10.1103/physrevb.72.235418
|View full text |Cite
|
Sign up to set email alerts
|

Experimental andab initiostudy of the structural and electronic properties of subnanometer thick Ag films on Pd(111)

Abstract: We present a combined, experimental, and computational investigation of the growth mode and the valenceband structure of Ag/ Pd͑111͒, with the focus on the Ag 4d derived quantum well states. Low-energy electron diffraction and scanning-tunneling microscopy are used to determine epitaxial, layer-by-layer growth of silver on the palladium substrate. High-resolution ͑in both energy and angle͒ photoelectron spectra and ab initio density-functional band-structure calculations are compared for 1 and 2 ML silver film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
(42 reference statements)
5
18
1
Order By: Relevance
“…1b). This result is consistent with prior scanning tunnelling microscopy (STM), 27,35 and two-photon photoemission 36 studies that indicate that Ag grows as a uniform twodimensional layer on Pd(111) at 300 K, starting at the palladium step-edges and expanding across the terraces until reaching a monolayer coverage. Prior STM images show only a small fraction of the Pd atoms remain uncovered, residing mainly at the step edges for a monolayer Ag deposited on Pd(111), consistent with the vibrational results ( Fig.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…1b). This result is consistent with prior scanning tunnelling microscopy (STM), 27,35 and two-photon photoemission 36 studies that indicate that Ag grows as a uniform twodimensional layer on Pd(111) at 300 K, starting at the palladium step-edges and expanding across the terraces until reaching a monolayer coverage. Prior STM images show only a small fraction of the Pd atoms remain uncovered, residing mainly at the step edges for a monolayer Ag deposited on Pd(111), consistent with the vibrational results ( Fig.…”
Section: Methodssupporting
confidence: 90%
“…1b). 35 This structure is thermally stable up to $500 K. 36 Carbon monoxide (CO) was also used to probe the amount of exposed surface palladium following deposition of lower coverages of Ag onto Pd(111) at 300 K. Since CO does not appreciably adsorb on silver at 300 K, 37 all CO signals can be attributed to adsorption on exposed Pd. For reference, a broad vibrational signal at 1924 cm À1 was obtained in the IR spectrum subsequent to 1.5 Langmuir (1 L ¼ 10 À6 torr s À1 ) of CO exposure on a clean Pd(111) single crystal at 300 K (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…12 (b-c)). A similar behavior was observed by Trontl [23] in the case of Ag growth on an atomically flat Pd(111) surface. Trontl also showed that Ag was weakly bound to the Pd substrate and followed a layer-by-layer step-flow growth mode thanks to the high mobility of Ag on Pd(111).…”
Section: Pd Growthsupporting
confidence: 59%
“…Pd(111)) [17,18,19,20,21,22]. However, while Ag grows layer-by-layer on Pd(111) [23], a columnar structure (i.e. islands with almost vertical edges) is formed upon Pd deposition on Ag(111) [19,20].…”
mentioning
confidence: 99%
“…Several studies report the detection of splike QW states in thin metal films [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], while comparatively few deal with d-derived QW states [5,8,[21][22][23][24][25][26][27][28]. Indeed, these states are difficult to resolve when the film thickness exceeds a few monolayers, due to the overlap of narrow d-bands with different symmetry.…”
Section: Introductionmentioning
confidence: 99%